Reduced soluble transferrin receptor concentrations in acute malaria in Vanuatu. - Williams, T; Maitland, K; Rees, D; Peto, T; Bowden, D; Weatherall, D; Clegg, J (1999)
Soluble transferrin receptor (sTfR) concentration is a sensitive index of iron deficiency when used in conjunction with ferritin measurements in adults. One advantage of this assay is that unlike ferritin it does not appear to be affected by a range of infectious and inflammatory conditions or by pregnancy, rendering it a promising adjunct to the diagnosis of iron deficiency in tropical populations. We have measured plasma sTfR concentrations in a group of malaria patients (n = 21) and asymptomatic (18) and aparasitemic (76) controls in Vanuatu. Plasma sTfR concentration was significantly reduced in individuals with acute malaria (P = 0.003). While this observation provides evidence that erythropoeitic suppression may be an important etiologic component in malarial anemia, it also suggests that malaria may be a confounding factor when interpreting sTfR concentrations in such populations. The role of sTfR in the diagnosis of iron deficiency in tropical populations remains to be established.